Effects of aflatoxins on male reproductive system: A review - KOUROUSEKOS (Γ.Δ. ΚΟΥΡΟΥΣΕΚΟΣ), G. D.; THEODOSIADOU (ΑΙΚ. Κ ΘΕΟΔΟΣΙΑΔΟΥ), E. Κ. (Journal of the Hellenic Veterinary Medical Society, 2018)
Mycotoxins constitute toxic substances produced by certain species of fungi. Among other mycotoxins, aflatoxins are considered to be really dangerous, since they are characterized as carcinogenic for animals and humans. The consumption of aflatoxins through feeds or foods could lead to deleterious effects on animals’ or humans’ health. Research on animals has shown that the general body condition as well as some of the blood parameters, mainly those of the liver could be negatively affected with aflatoxin administration. Regarding the reproductive system, although not extensively studied, some investigators support the negative effects of aflatoxins either on females or on males. More specifically, in male, the size and weight of the genital organs, the spermatogenesis, the number, the motility and the morphology of sperm cells as well as hormones’ concentrations could be affected after exposure of the animals to aflatoxins, making infertility problems more frequent. Most studies refer to laboratory and less to productive animals, while only two studies refer to the possible problems of infertility on men due to aflatoxins. Since reproduction consists one of the most important sectors of animal husbandry, special attention should be paid to nutrition so that the possibility of the aflatoxin consumption by animals would be eliminated, the animal health especially regarding the reproductive system would be protected and economic losses would be ameliorated.